The reflection of the accounting disclosure on social responsibility in evaluating the performance of economic units (Entrepreneurship Journal for Finance and Business, 2021)
This research was conducted in one of the general directorates of the Iraqi Ministry of Electricity, which is the General Directorate of Rusafa Electricity Distribution, for three years (2015, 2016, and 2017). The research focused on the problem of lack of interest in the accounting disclosure of social responsibility in the financial statements in the aforementioned directorate.The aim of the research is to demonstrate the role of accounting disclosure on social activities carried out by economic units in the financial financial statements, in addition to explaining the role of accounting disclosure on social activities in evaluating the performance of economic units,The research, through measuring social performance indicators that include financial performance and non-financial (social) performance, reached conclusions, the most important of which is the lack of accounting disclosure about the costs and expenditures of social responsibility despite the fact that the General Directorate for Distribution of Al-Rasafa Electricity bears the expenses of its social performance.The researcher recommended the necessity of enacting laws and instructions that oblige economic units to pay attention to social performance and allocating the necessary sums in the state’s general budget and disclosing them in the financial statements in order to achieve the goal of social responsibility, which is to achieve the gains that can be achieved. These units are in their nature units aimed at achieving profits.